PENENTUAN PRIORITAS PESERTA PELATIHAN DIGITALISASI UMKM MENGGUNAKAN METODE ADDITIVE RATIO ASSESSMENT - Sugara, Heru; Purba, Arifin Tua (Jurnal Tekinkom (Teknik Informasi dan Komputer), 2023)
Digitalization of UMKM is the key to increasing the competitiveness of UMKM in the current technological era. This research aims to create priorities for UMKM digitalization training participants in Pematang Dolok Kahean Village. Determining basic priorities for training participants is carried out using the Decision Support System (DSS) with the Additive Ratio Assessment (ARAS) Method. The criteria used are Business Relevance, UMKM Digital Knowledge and Skills, Potential for Increased Income, Implementation Costs, and Implementation Time. The weight of each criterion is determined based on preference and relative importance. The research results show that alternative A5 is in first position with a result of 0.972, A7 is in second position with a result of 0.921, and A4 is in third position with a result of 0.872. The results of designing a Decision Support System (DSS) to determine priorities for digitalization training for UMKM can help make it easier for the Head of Pematang Dolok Kahean Village to determine priorities for digitalization training for UMKM.